2018
DOI: 10.22547/ber/10.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Behavioral Intention towards Mobile Learning in Pakistan: Mediating role of Attitude

Abstract: Mobile learning is an emerging concept which has been verified in previous years. With the rapid advancement in mobile technology, it has emerged with new facets that have significant impact on attitude and behavioral intention towards mobile learning. The purpose of the study is to measure the factors that can affect the behavioral intention towards mobile learning in Pakistan. Mediating role of attitude and direct relationshi p of entertainment, informativeness and irritation are measured. Simple random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Irritation is a phenomenon pretty much similar to reactance, where the consumer is more likely to reject advertisements perceived as intrusive (Hameed and Qayyum 2018). Edwards et al, (2002) observed irritation as a possible emotional reaction and avoidance as a potential behavioral outcome in response to intrusive advertising.…”
Section: Irritation Appeal/product Categoriesmentioning
confidence: 99%
“…Irritation is a phenomenon pretty much similar to reactance, where the consumer is more likely to reject advertisements perceived as intrusive (Hameed and Qayyum 2018). Edwards et al, (2002) observed irritation as a possible emotional reaction and avoidance as a potential behavioral outcome in response to intrusive advertising.…”
Section: Irritation Appeal/product Categoriesmentioning
confidence: 99%
“…This theory has not specifically applied to this context. The suggestions by Mohammadi ( 2015b ) are incorporated to unveil the impact of U&G theory in the mobile learning context as previously the TAM and IS model was incorporated (Hameed & Qayyum, 2018 ). BITML is the untouched part as mandated by Chen ( 2011 ); Cheok and Wong, ( 2015 ); Reychav and Wu ( 2015 ); Reychav et al, ( 2016 ); and Wong et al, ( 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it is essential to comprehend the underlying mechanisms by which behavioral intentions toward mobile learning (BITML) may be influenced by perceived entertainment, informativeness, irritation, trust, and value. The extant literature indicates that attitude mediates the association between a variety of predictors, such as entertainment, relaxation, escape time, value, and quality, and dependent variables, such as behavioral intention, purchase intention, and buying intention (Curras-Perez et al, 2014 ; Hameed et al, 2018 ; Mohammadi, 2015a ; Zhu & Chang, 2014 ); however, mediating role of attitude between perceived entertainment, informativeness, irritation, trust and value, and BITML has not been explored yet. Therefore, in order to provide a more comprehensive picture, this study aims to investigate the impact of the five factors described above on attitude toward mobile learning (ATML), which in turn influences BITML and mediating role of ATML between relathionship of entertainment (ENT), informativeness (INF), irritation (IRR), trust (PERT), value (PERV), and BITML.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous analysis has demonstrated that the effects of promotional messages are potentially influenced by publicity and brand behaviour (Kaushal & Kumar, 2016). Different researches on the online environment have identified the mediating role of attitudes in the relationship between website encouragement and desire to buy online (Shaouf et al, 2016;Redondo & Aznar, 2018;Hameed & Qayyum, 2018). The attitude of the customer online through the online shopping channel is either positive or negative as an appraisal outcome.…”
Section: The Mediation Role Of Attitudementioning
confidence: 99%